Integration and demonstration of data acquisition and control of sensor data in open system interconnection model of industry 4.0 - Mikael Ndaru Ajiwidodo (Nanyang Technological University, 2023)
The advanced development of internet technology, one of which is IoT, is very applicable to many industries. One system that uses IoT is EMS, a system that manage the energy usage of the observed system. With quick and precise algorithms, EMS works better to make decisions for the system to utilize the energy wisely. This report describes the improvement of IoT software application that supports the EMS. There are two software that were developed using different protocols, OPC UA and FTP. The first software application is an OPC UA client that gather all data of the OPC UA server and send it to the EMS over the internet through MQTT protocol. The second software application is an FTP client that only have seven commands which are login, get file list, change directory, store file, delete file, keep alive, and quit. After the software design phase, these software are developed within a Linux environment with Python and C/C++ programming language. Implementation of the software are explained in detail by using tables and diagrams. After the development, demonstrations were successfully conducted for both software application. OPC UA software application was demonstrated by integrating three OPC UA push clients and OPC UA server while the OPC UA pull client fetch the data from the OPC UA server and publish it to a topic of a MQTT broker while another MQTT client tried to subscribe to the topic. Meanwhile, FTP client was demonstrated by using test cases to make sure that the implemented FTP client class works as intended. Even though it was successfully executed, there are some aspects that can be improved for both software. Multiple proper test cases can be added for the OPC UA software to properly check the software behaviour. Also, more functions can be added to the FTP client class to broaden the usage which also meant adding more test cases.